Eat to live quick & easy cookbook : 131 delicious, nutrient-rich recipes for fast and sustained weight loss, reversing disease, and lifelong health - Fuhrman, Joel (HarperOne, an imprint of HarperCollinsPublishers, 2017)
"Discover What Millions of People Have Already Experienced-- Dr. Fuhrman's Extraordinary and Life-Changing Recipes. Too busy to shop? Too tired to cook? Not sure what's healthy? From the #1 New York Times best-selling author of Eat to Live and the instant New York Times bestseller Eat to Live Cookbook comes Eat to Live Quick and Easy Cookbook, 131 super delicious, easy-to-prepare, incredibly healthy recipes. No guilt, no-fuss, just amazing food that's good for you. From the grocery store to the kitchen table, Eat to Live Quick and Easy Cookbook is just what you and your family have been looking for to become happier and healthier than ever before"--